Kesiapan Lembaga Pelaksana dan Bentuk Implementasi Pidana Kerja Sosial di Provinsi Daerah Istimewa Yogyakarta - ulul albab, wildan; Safitri, Masna Nuros; Insyaniyah, Inarotul (Indonesian Journal of Criminal Law and Criminology (IJCLC), 2025)
The main punishment mentioned in Law Number 1 Year 2023 on the Criminal Code consists of imprisonment, closure, supervision, fine and community service. The renewal of the types of basic punishment, in this case social work punishment, certainly requires institutional readiness in its implementation and supervision. In this study, the researcher will examine how the concept of the implementation of social work punishment in Criminal Law Reform in Indonesia and how the challenges of implementing agencies in the framework of implementing social work punishment as a form of punishment in national criminal law reform. The research method used in this research is Normative Empirical. The research concludes that the form of social work punishment in Law Number 1 Year 2023 on the Criminal Code is by means of criminal offenders being required to carry out work or social activities that are beneficial to the community within a certain period of time. The challenges that will be faced by the government in relation to the implementation of social work punishment mainly lie in the unavailability of facilities and infrastructure and the lack of coordination between institutions implementing social work punishment. In addition, the difficulty also lies in the fact that the Government Regulation has not been ratified as an implementing regulation regarding social work punishment, so that the institutions implementing social work punishment cannot be sure of the concept and form of implementation of social work sanctions.